ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERDAGANGAN MINYAK INTI SAWIT INDONESIA DI NEGARA IMPORTIR UTAMA - Rizki Amalia; Harianto Harianto Harianto; Amzul Amzul Rifin (Pusat Penelitian Kelapa Sawit, 2019)
As one of the largest producers in the world, Indonesia has an interest in increasing the share of palm kernel oil exports which are being faced with negative issues from vegetable oil producer countries towards the palm oil industry and its derivatives; on the other hand maintaining the availability of domestic PKO as industrial raw material. This study aims to analyze the factors that influence the performance of Indonesia's palm kernel oil trade. The study used dynamic simultaneous equations and consist of 18 behavioral and 25 identities equations using time series data from 1990 to 2017 . The estimation results indicate that changes in the supply of Indonesian palm kernel oil exports to the main export destination countries are responsive to changes in palm kernel oil mature area, technology improvement, and downstream dummy policies. Meanwhile, the demand of the main importers of palm kernel oil is responsive to changes in world palm oil prices, per capita income of the country's, and world crude oil prices. The downstream policy accompanied by improvements in technology, infrastructure, and the business climate is needed to improve the efficiency of the domestic palm kernel oil industry and reduce dependence on exports.